2022
DOI: 10.1017/s1041610222000126
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in dementia: associations with neuropsychiatric symptoms and subtype diagnosis

Abstract: Objectives: To investigate factors associated with suicidal ideation (SI) around the time of dementia diagnosis. We hypothesised relatively preserved cognition, co-occurring physical and psychiatric disorders, functional impairments, and dementia diagnosis subtype would be associated with a higher risk of SI. Design: Cross-sectional study using routinely collected electronic mental healthcare records. Setting: National Health Service secondary mental healthcare services… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Another study reported that depression, constipation, and lower instrumental ADL were associated with lower QOL in patients with DLB [11], and ADL has also been identified as a key factor for QOL in patients with dementia [13]. Regarding depression, DLB is associated with a relatively high rate of depression as a complication [28] and patients are at a higher risk of suicide compared with other types of dementia [29]. Furthermore, a previous study reported that older people with depression have decreased walking function and decreased life function [30], which can reduce the activity of patients with DLB and impair their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that depression, constipation, and lower instrumental ADL were associated with lower QOL in patients with DLB [11], and ADL has also been identified as a key factor for QOL in patients with dementia [13]. Regarding depression, DLB is associated with a relatively high rate of depression as a complication [28] and patients are at a higher risk of suicide compared with other types of dementia [29]. Furthermore, a previous study reported that older people with depression have decreased walking function and decreased life function [30], which can reduce the activity of patients with DLB and impair their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We further conducted sensitivity analysis considering suicide as outcome and including either sociodemographics (model 1) or prescribed medications (model 2). We also investigated the risk of SB considering Alzheimer’s disease and other types of dementia as differential risk of suicidal ideation by dementia subtype has been reported (Naismith et al ., 2022), and as it was thought that patients with non-Alzheimer dementia may be at increased risk due to the association of these subtypes with neuropsychiatric symptoms such as depression, hallucinations, and delusions (Armstrong et al ., 2021; Haw et al ., 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Also, since the majority of data on diagnoses, dementia, and suicide risk derive from cohort studies, it is difficult to understand how suicide and dementia converge in the clinic setting. In this issue of International Psychogeriatrics, Naismith et al, (2022) investigate whether natural language processing (NLP) applied to free text in the Electronic Health Record (EHR) could add to the understanding of dementia and suicide risk. Naismith et al's (2022) study is notable both for its results as well as the means by which the results were derived.…”
mentioning
confidence: 99%
“…First, NLP systems are subject to a tradeoffsimplistic but transparent, or, sophisticated but difficult to assess the performance or perform replication (Naylor et al, 2021). The study (Naismith et al, 2022) derived associations between dementia subtypes and incidence of suicide ideation using NLP techniques on free-text fields. Using a relatively simple discoverable term matching method to identify records for suicide ideation while the diagnosis was identified based on coded fields, the study draws strength from both transparency and replicability.…”
mentioning
confidence: 99%
See 1 more Smart Citation